Short-term Uresta efficacy (SURE) study: a randomized controlled trial of the Uresta continence device. (January 2017) - Lovatsis, Danny; Best, Carolyn; Diamond, Phaedra
Abstract Introduction and hypothesis An intravaginal device (Uresta) is currently available for the treatment of stress urinary incontinence (SUI). Case-series data on its effectiveness exist; however, controlled data are lacking. The objective of this study is to determine the short-term efficacy of the Uresta device using a randomized placebo controlled trial. The hypothesis is that the Uresta device might significantly reduce urinary loss. Methods A single blind randomized controlled trial was conducted among women with urodynamic SUI recruited from a single urogynecology unit. Participants were randomized to receive the Uresta device or a placebo vaginal silastic ring placed high in the vagina for the duration of a pad test. Pad tests were performed before and after device placement. The primary outcome was the achievement of a 50 % or greater reduction in pad weight after device placement, in a comparison of the two groups. Sample size calculation showed a need for 18 subjects per group. Fisher's exact test was used to analyze the primary outcome. Research Ethics Board approval was obtained. Results Eighteen subjects per group completed the study protocol. The percentage of patients who achieved the primary outcome was 66.7 % in the Uresta group and 22.2 % in the placebo group (p  = 0.01). The baseline demographic data were similar in the two groups. There were no adverse events during the test period. Conclusions The Uresta intravaginal continence device significantly reduces the short-term objective measures of urine loss due to SUI. Further study to assess subjective outcomes and long-term patient satisfaction is required.